Studi Kasus Perubahan Termoregulasi BBLR Dalam Perawatan Metode Kanguru Di Ruang NICU RS Siti Khodijah Muhammadiyah Cabang Sepanjang - yumni, fathiya luthfil (Universitas Muhammadiyah Surabaya, 2022)
Low birth weight (LBW) is a newborn with a weight < 2500 grams regardless of gestational age. LBW is one of the main causes of death, morbidity and disability in neonates. The problem that often occurs in LBW is disturbed thermoregulation. Disorders of thermoregulation can be in the form of hypothermia.Objective: This case study studies how the thermoregulation of low birth weight changes in kangaroo care in the NICU room of Siti Khodijah Muhammadiyah Hospital branch Sepanjang.Methods: The research uses a case study approach. The sample of this study was 2 LBW respondents. The final result of direct observation at the time of PMK and written on the observation sheet. The unit of analysis in this case study is the characteristics of LBW, the success of PMK, and changes in LBW thermoregulation with PMK.Results: The results of the two respondents in the LBW category were marked by birth weight between 1501 grams - 2499 grams with gestational age < 37 weeks, the success of the successful PMK category was marked by an increase in body temperature, slow sucking reflex, no vomiting, maternal milk production between 10-15 cc/2 hours, The baby's weight was fixed, and changes in LBW thermoregulation in the PMK category of normal/stable body temperature were proven to have an increase in temperature before PMK was carried out until the first 1 hour of PMK.Conclusion: Changes in the thermoregulation of LBW in the PMK of the two respondents, there was an increase in body temperature/stable during the first 1 hour of PMK